2018
DOI: 10.30955/gnj.002525
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microorganisms in Permeable Reactive Bio-Barriers (PRBBs) for Environmental Clean-Up: A Review

Abstract: It is an indisputable fact that any environmental clean-up technology generating certain kind of effective result would be easily supported. One of them includes Permeable reactive bio-barrier which is an innovative technology started from 90's to treat a variety of contaminants along the natural gradient flow of groundwater through immobilization or transformation of pollutants into less toxic and harmful form. Despite of any broad acknowledgement, there are lesser known knowledge about use of microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Andrade et al mainly discussed the single-action mechanism of four fillers (ZVI, activated carbon, zeolite, and microorganisms) and focused on organic compounds in soil . Upadhyay et al introduced the mechanism of removal of permeable reactive biobarriers (PRBB) for nitrate, heavy metals, chlorinated solvents, and hydrocarbons (arsenic, vanadium, uranium, selenium, and emerging contaminants were not discussed), and the microbe–filler interaction was not discussed . Original insights into the different types of active media and microbial carriers, the design and reaction rate of Bio-PRBs, and the mechanisms of interaction among 30 species of microorganisms, active media, and comprehensive and representative contaminants were provided.…”
Section: Advances In Bio-prb Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Andrade et al mainly discussed the single-action mechanism of four fillers (ZVI, activated carbon, zeolite, and microorganisms) and focused on organic compounds in soil . Upadhyay et al introduced the mechanism of removal of permeable reactive biobarriers (PRBB) for nitrate, heavy metals, chlorinated solvents, and hydrocarbons (arsenic, vanadium, uranium, selenium, and emerging contaminants were not discussed), and the microbe–filler interaction was not discussed . Original insights into the different types of active media and microbial carriers, the design and reaction rate of Bio-PRBs, and the mechanisms of interaction among 30 species of microorganisms, active media, and comprehensive and representative contaminants were provided.…”
Section: Advances In Bio-prb Technologymentioning
confidence: 99%
“…According to the properties of contaminants, the Bio-PRBs can be designed to be single or multiple microorganism augmentation barriers to meet the requirements. , In addition, these reported microbial populations [e.g., Mycobacteria , Pseudomonas , and Sphingomonas , sulfate-reducing bacteria ( Desulfitobacterium hafniense Y-51 and Geobacter metallireducens GS-15), Desulfitobacterium , Sulfurospirillium , and Desulfuromonas , nitrobenzene (NB)-degrading bacteria, and arsenate-reducing bacteria ( Clostridium )] have been added to Bio-PRBs for the efficient removal of specific contaminants [e.g., PHE, TCE, NB, As­(V), and As­(III)].…”
Section: Introductionmentioning
confidence: 99%
“…Scherer et al 21 provide a review of PRBs for groundwater treatment using chemical and biological methods. Upadhyay and Sinha 22 reviewed permeable reactive biobarriers (PRBBs) for environmental clean-up. For aerobic treatment, barriers have focused on contaminants that can be metabolized, such as BTEX, through the addition of slow-release forms of oxygen-releasing compounds (ORCs) such as calcium or magnesium peroxides.…”
Section: Introductionmentioning
confidence: 99%
“…used column experiments to explore the factors affecting the removal efficiency of benzene and toluene.The results showed that the activity of microorganisms could not be ignored. In order to improve the bioremediation efficiency of oil contaminated groundwater,Lee et al (2019) injected an emulsified colloidal matrix suspension into the groundwater, which directly promoted the increase in the total number of bacteria and the rapid decline of benzene concentration Upadhyay & Sinha (2018). systematically analysed and summarized the role of microorganisms in PRB, they believed that the symbiotic relationship with the reaction medium was the key to the performance of PRB.…”
mentioning
confidence: 99%